Econometric analysis of foreign reserves and some macroeconomic variables in Nigeria (1970–2007) - Olokoyo, Felicia O; Osabuohien, Evans; Salami, O Adeleke (African Development Review, 2009)
P¿Countries are showing interest in accumulating foreign reserves to ensure macroeconomic stability. There has been some debate whether to beef up the level of nations' foreign reserves or make it lower, especially in developing countries like Nigeria. Whereas some argue that the foreign reserve determines the country's rating in the global market, others hold opposing views. In this light, this paper examined the interactive influence of foreign reserve (FRS) on some macroeconomic variables such as: economic size (GDP); trade; level of capital inflows (KFL); exchange rate (EXR); and inflation. Analyzing secondary data from CBN statistical bulletins (1970-2007), the econometric results obtained from cointegration test, vector error correction (VEC) within the framework of autoregressive distributed lags (ARDL) revealed the following: (1) existence of a long-run relationship between the variables and two cointegrating equations; (2) possibility of convergence of the variables from the short run to the long run with slow speed of adjustment. It is thus the conclusion of this paper that accumulation of large foreign reserves is not very productive in Nigeria due to its inability to induce some of the macroeconomic variables.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-248-861-812-930 tex.type: [object Object]
Keywords: dept.eco; dept.fin